Analisis Fikih Muamalah terhadap Praktik Bisnis Waralaba (Franchise) di Indonesia: Kajian Akad, Royalti, dan Lisensi Merek - Revania Putri Ramadhani; Siti Kulsumiat; Syaeful Bahri (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2026)
The development of the franchise business in Indonesia has created a business cooperation model that allows the use of trademarks, operational systems, and intellectual property rights through specific agreements. This study examines franchise practices from the perspective of fiqh muamalah, focusing on contracts, royalty payments, and the validity of trademark licenses. The research aims to describe franchise business practices in Indonesia, analyze the position of contracts within the franchise system, examine royalties as compensation for the use of benefits, and assess the validity of trademark licenses based on fiqh muamalah principles. This study employs a descriptive qualitative method with a library research approach. Data were analyzed through content analysis using secondary sources, including the Qur’an, Hadith, fiqh muamalah literature, franchise regulations, intellectual property references, and relevant scientific journals. The findings show that franchise contracts can be understood through syirkah and ijarah contracts, which are consistent with fiqh muamalah principles. Royalties are considered lawful compensation for the use of trademarks and business systems with economic value, while trademark licenses are valid contract objects as recognized intellectual property rights. Franchise practices are permissible in Islam as long as they uphold justice, transparency, and avoid elements of gharar, riba, and maisir.